Google Translate As an Alternative Tool to Assist EFL Undergraduate’s Students’ Assignment - Arjulayana Arjulayana (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2019)
This study aimed to present the data analysis regarding assistance tools for EFL undergraduate students in completing their assignments. In the digital era, the use of google translation is one of the most popular tools among EFL students, either for their assignment or improve foreign language’ skills. EFL undergraduate students of University Muhammadiyah Tangerang in 5th-semester areas the research subject, because most of them should complete their assignment and almost of their subject lesson should use English weather orally or written form. This research used purposive sampling with a total is 35 students, and a qualitative descriptive method is used to analyze and present the data comprehensively. The data collection starts from problem identification, field observation, interview and study document be based on their assignment submitted.